Cultivation of spirulina using aquaculture wastewater as an alternative nutrient source - Nur Muhammad Faiz Bin Adnan (Nanyang Technological University, 2024)
Spirulina is a cyanobacteria used in various supplementation for consumption, cosmetics and wound healing. This project aims to reduce the need for synthetic medium supplementation by using aquaculture wastewater as an alternative nutrient source to reduce Spirulina cultivation costs. Two experiments were conducted for their biomass production and cost-effectiveness. The cultivation period was 2 weeks. The first experiment aims to eliminate using synthetic mediums. The result showed that full aquaculture wastewater (W100) has the highest biomass cultivation, indicating an alternative potential nutrient source. The second experiment used full aquaculture wastewater with varying concentrations of synthetic mediums from 25% and below. The result showed that 10% of the modified Zarrouk’s medium (S10) had the highest biomass absorbance at the end of the experiment. Further discussion addressed better biomass production for 1 week and 2 weeks of cultivation. The results showed that 5% culture medium with aquaculture wastewater (S5) (0.544 A) has the highest biomass absorption after 1 week than S10 (0.529 A). However, their differences are not significant (0.015 A). S10 has the highest biomass after 2 weeks of cultivation while maintaining the growth after Day 13. However, S5 dies off after Day 13 of cultivation. Thus, S10 has potential usage for efficient growth for Spirulina while reducing the cost to about 90% savings. More studies should be made for the feasibility of the results such as various wastewater collection venues and larger scale volumes like using large tubs of water for easier medium calculation.